Dried spot cards to analyse biologic fluids for diagnostic investigation of patients - Rapulana, Antony Morwamoche (Division of Chemical Pathology, 2019)
Background: Collection of biologic fluid for laboratory analysis requires relatively large samples, often with additives, and transport in fragile tubes. The analytes or matrices may be unstable so testing needs to be carried out quickly. Collection of these biologic fluids and drying them on filter paper can lower the cost of transporting the sample to the laboratory, avoid instability of the matrix, and degradation of the analytes. Aim: The aim of this project was to develop an inexpensive, convenient, comprehensive and reproducible patient sample collection system which ensures integrity and ease of transport of small-scale samples at room temperature, as well as ensuring convenient long-term storage for subsequent analysis. Methods: Samples (blood, buffy coat, serum, plasma and urine) were collected into various tubes and spotted onto filter paper cards. Concentrations of total cholesterol, triglyceride, phospholipids, glucose, lactate, and protein were measured in the original sample and dried plasma spots (DPS) and the concentration of creatinine was measured in urine and dried urine spots (DUS). Determination of oxidation of lipids by measurement of conjugated dienes (CD) and thiobarbituric acid reactive substances (TBARS) on dried serum spots (DSS) was carried out. Determination of salicylate on serum and dried serum spots and cyanide on whole blood and dried blood spots was carried out. Values obtained from original samples and dried spots were compared. In addition, DNA extracted from a dried buffy coat spot (DBCS) from a familial hypercholesterolemia patient was analysed after spotting. Results: The total cholesterol, triglyceride, phospholipid, glucose, lactate and protein concentration values of 14 samples were compared in whole plasma and DPS stored at different temperatures. These were highly correlated after 1 week and 3 months of collection and storage. Plasma cholesterol, glucose and lactate concentration values for DPS as well as urinary creatinine for DUS at 1 week were not significantly different to that at both 3 and 7 months’ analyses (p>0.05). Plasma triglyceride and phospholipid concentrations were significantly different (p blood vs DBS respectively) for cyanide. Salicylate in DSS and cyanide in DBS were not significantly different to the original samples (paired t-test, p>0.05). Conclusion: Dried filter spots may be used to transport and store biologic fluid samples for analyses of a number of water-soluble and water-insoluble analytes. To protect lipids from being oxidised, the filter paper should be pre-treated with BHT.